A computational analysis of dissipation effects on the hydromagnetic convective flow of hybrid nanofluids along a vertical wavy surface. Issue 8 (27th July 2021) - Iqbal, Muhammad Saleem; Mustafa, Irfan; Ghaffari, Abuzar; Usman,
Abstract: Hybrid nanofluids (HNFs) are innovative nanofluids produced by adding various types of nanoparticles to the base fluid. A mathematical analysis of flow and heat transfer of hydromagnetic HNF along a vertical wavy texture is performed in this article. The effects of viscous dissipation are also encountered in the present study. The considered HNF was composed of two nanoparticles, copper and titania. The mathematical modeled partial differential equations are transformed into dimensionless nonsimilar forms. The results obtained for the HNF were compared with those for the  Cu ‐ and TiO 2 ‐based nanofluid with the help of a well‐known numerical procedure, the Keller‐box scheme. On nonflat (wavy) texture, the Nusselt number is higher as compared with a flat sheet. The Nusselt number is higher for Cu nanoparticles relative to Ti nanoparticles. For increased wavy amplitude and magnetic parameter Mg values, a reduction in the coefficient of skin friction and Nusselt number is expected.